Case report: From negative to positive: a remarkable journey of ER, PR and HER2 status in a patient with metastatic breast cancer - Huang, Jiaqi; Liu, Lan; Ding, Jianghua (Frontiers in Oncology, 2024)
Breast cancer is the most common malignant tumor in women, posing a serious threat to women's health. HER2 has been identified as a key oncogene and prognostic factor in breast cancer. Recent studies have reported inconsistencies in ER, PR, and/or HER2 expression between primary breast tumors and metastatic lesions. Rarely is it reported that all three biomarkers experience conversion. In this report, we present the case of a female patient with relapsed and metastatic breast cancer, whose histology transformed from initially triple-negative to Luminal-B type (HER2 positive) (i.e., ER, PR, and HER2 positive). She underwent systematic chemotherapy, targeted therapy, and cranial radiotherapy, which was followed by maintenance treatment with targeted and endocrine therapy. Currently, she has been in nearly complete remission (nCR) for more than 12 months. For recurrent and metastatic breast cancer, it is necessary to perform the second biopsy for metastases, which would contribute to precision treatment and prognosis improvement.